O PROCESSO DE ADOÇÃO DO BIM EM UMA CONSTRUTORA DE GRANDE PORTE DE SÃO PAULO - Freitas, Raissa Caroline Faria; Melhado, Silvio Burrattino (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The BIM adoption process is challenging, since there are many approaches to its implementation, and it relies on the company's objectives, strategies and willingness to modify its own working method. Moreover, there are several stages that are crucial for the methodology rollout success and to guarantee that the implementation objectives are met. As well as any other massive processes change, BIM deployment raises concern and resistance on the company's professionals, therefore understanding the meaning of the methodology and how this implementation is going to impact their working process is fundamental for all employees. That being said, the purpose of this article is to report the experience of a large construction company during its BIM adoption process and to analyze the deployment phases, the key issues to achieve the expected goals and the challenges encountered during this process. From the case study it was possible to understand that, despite the different paths to implement BIM in a company, it is essential to focus on the design of the apdoption process, the planning of the process change and the employees cultural preparation.